AB1260 Baseline characteristics and patient satisfaction data from coach@home: the german support program for patients with rheumatic diseases treated with certolizumab pegol. (12th June 2018) - Böhme, N.; Holst, A.-D.; Dybowski, F.; Volberg, C.; Pott, H.-G.; Lendl, U.
Abstract : Background: Certolizumab pegol (CZP)-treated patients (pts) with rheumatoid arthritis (RA), axial spondyloarthritis (axSpA, including ankylosing spondylitis [AS] and non-radiographic [nr-]axSpA), and psoriatic arthritis (PsA) may be recommended the patient-coaching program, coach@home (c@h) in Germany to manage their disease. Eight coaching calls are offered over one year, scheduled around 'critical' milestones along the therapeutic journey. These calls are made by professionally-trained nurses, who offer support and information about both the disease and its treatment with CZP. Objectives: The purpose of this observational analysis was to assess the baseline characteristics of pts subscribed to c@h, and the level of pt satisfaction with the program. Methods: c@h was launched in, June 2014 and is available to pts who are prescribed CZP according to the local product label. Pts must be CZP-naïve when subscribed to the program, and pt consent is required prior to subscription by the treating physician. There are no additional criteria for enrolment, although the program must be recommended to the pt by the treating physician. Pt satisfaction was measured either at the end of the program or at discontinuation using the net promoter score (NPS), which has previously been used for this purpose. 1 The NPS is derived by asking pts to state how likely it is that they would recommend c@h to others (on a 0–10 scale). Rankings of 9–10 are considered 'promoters', 7–8 'passives', and 0–6 'detractors'. Subtracting the percentage of detractors from that of promoters yields the NPS (figure 1). Results: A cumulative total of 655 pts had been registered to the program as of 5 . Oct 2017 Of the total number of reported indications (n=683; multiple indications per pt possible), 55.9% were RA, 16.5% AS, 7.6% nr-axSpA, and 19.9% PsA. The mean age at baseline was 55 (RA), 54 (AS), 53 (nr-axSpA), and 52 (PsA), and the proportion of female pts was 80%, 58%, 65%, and 69%, respectively. Prior biologic DMARD exposure was 32.8%. The most common topics discussed on phone calls were therapy compliance (in 1339 calls), CZP maintenance dose (in 1333 calls) and syringe disposal (in 870 calls). The average length per call was 15.9 min at the end of Week 0 (total: 28 calls), and 14.0 min at the end of Week 52 (total: 1796 calls). A cumulative total of 272 pts had either completed the 1 year coaching period (n=70) or discontinued (n=202) by 28, Sep 2017 of whom 106 rated the program. Of these, 87.5% gave promoter scores, 10.4% passive, and 3.8% detractor, yielding an NPS of 83.7 (figure 1). The program was still ongoing at the time of this data cut. Patients were asked to rate the coach@home program on a scale of 0–10, where 0="I would certainly not recommend this program" and 10="I would most probably recommend this program". Scores of 9–10 were considered 'promoters', 7–8 'passives' and 0–6 'detractors'. Percentages shown are out of the total number of responders by the end of September 2017 (n=106). NPS: Net Promoter Score. Conclusions: The c@h program offers guidance and support to pts treated with CZP in Germany. Feedback from pts who were willing to provide a rating indicates a high level of satisfaction with the program. Reference: [1] Hamilton DF. Bone Joint J 2014;96-B(5):622–8. Acknowledgements: The c@h program is performed by Healthcare@home Deutschland GmbH, funded by UCB Pharma, led by Elke Zeise and managed by Karen Thiel and Manh Dan Nguyen. We thank the patients and their caregivers in addition to the investigators and their teams who contributed to this program. Editorial services were provided by Costello Medical. Disclosure of Interest: N. Böhme: None declared, A.-D. Holst Grant/research support from: AbbVie, BMS, Chugai, Pfizer, Paid instructor for: BMS, Lilly, UCB Pharma, F. Dybowski: None declared, C. Volberg: None declared, H.-G. Pott Paid instructor for: Hexal, Lilly, Novartis, MSD, Speakers bureau: AbbVie, Biogen, Chugai, Roche, Pfizer, Celgene, UCB Pharma, Medac, U. Lendl Employee of: UCB Pharma